Marx and Tocqueville: From the February revolution to Louis Bonaparte's coup d'état, approximations and contrasts in the French political process in the mid-19th century (Research, Society and Development, 2024)
This research aims to compare the theories of Marx and Tocqueville regarding the mid-19th century political events in France that led to the February Revolution of 1848 carried out by the Parisian proletariat and how this same proletariat would be crushed by the bourgeoisie in the June Days of the same year, causing a shift in social classes that culminated in the coup d'état of Louis Bonaparte in December 1851, supported by the mass of the bourgeoisie.This is a strictly bibliographic and literature review research, based on Marx's The Eighteenth Brumaire of Louis Bonaparte and Tocqueville's Recollections of 1848, supported by several authors and commentators of these classical authors. As a result of our research, we found that, despite the methodological and class differences that separate the two classical thinkers, their analyses converge on crucial points, such as the characterization of the February Revolution as a socialist one with the proletariat as the main social force that overthrew the Orleanist Monarchy, as well as the general causes and accidents that enabled the outbreak of the revolution and all the chains of events that culminated in the coup d'état of Louis Bonaparte and put an end to the French revolutionary process.